PEMANFAATAN SISTEM INFORMATIKA, TATA KELOLA WISATA DAN SMART TOURISM TERHADAP PROMOSI PARIWISATA, STUDI KASUS PARIWISATA DI SINGAPURA - Tirtosetianto, Raden Hario; Sonya, Anggita; Widiastuti, Hastirin (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2024)
This study centers on the utilization of information systems, tourist administration, and the notion of smart tourism to enhance tourism promotion in Singapore. This research employs a qualitative methodology to investigate the application of different technologies and governance practices in order to enhance the effectiveness of tourism promotions and their impact on tourists' perceptions and experiences. Data was gathered in Singapore through a case study, utilizing in-depth interviews and participant observation techniques. The stakeholders involved in the tourism industry, such as destination managers, tourists, and government regulators, were the sources of this data. Thematic analysis is employed to investigate perspectives, encounters, and the consequences of deploying information technologies and smart tourism on strategies for promoting tourism. The research results demonstrate that the utilization of information systems and smart tourism technologies in Singapore significantly enhances the visibility and allure of tourist attractions. This technology facilitates the customization of promotions, immediate interactions, and the delivery of timely and pertinent information to tourists. In addition, efficient tourism governance facilitates cooperation among stakeholders, enhances planning, and ensures successful deployment of technology, all of which result in more effective tourism promotion. The notion of smart tourism, encompassing technology advancements including big data, Internet of Things (IoT), and artificial intelligence (AI), has been discovered to significantly impact the visitor experience by enhancing comfort, giving comprehensive information, and delivering superior services. The integration of information systems, tourism governance, and smart tourism results in the development of promotional techniques that are inventive, adaptable, and highly responsive to the demands of the tourism market.